P88 Real-world effectiveness of anti-IL-5/5R therapies in severe atopic eosinophilic asthmatics eligible for anti-IgE therapy. (12th November 2019) - Jackson, DJ; Kavanagh, J; Roxas, C; D'Ancona, G; Green, L; Thomson, L; Fernandes, M; Dhariwal, J; Nanzer, AM; Kent, BD
Abstract : Introduction: A significant proportion of adult patients with severe eosinophilic asthma (SEA) have evidence of both atopic and eosinophilic airways inflammation and meet eligibility criteria for all 4 NICE-approved biologic therapies. In the absence of randomised head-to-head studies comparing omalizumab and an anti-IL5/5R therapy, physicians lack a robust evidence base for choosing between these two classes of treatment. To date there are no real-world effectiveness data reporting clinical outcomes of mepolizumab and benralizumab in patients also eligible for omalizumab. Methods: We retrospectively assessed all SEA patients at our tertiary asthma centre treated with either mepolizumab or benralizumab for a minimum of 24 weeks. Eligibility criteria for omalizumab, including whether patients could be dosed adequately based on weight and IgE levels, were recorded. Clinical outcomes at 24 weeks were compared between patients eligible and ineligible for omalizumab. Results: One hundred and fifty-seven patients (46.7% female, mean age 51.7±14.3, 58.9% atopic) treated with either mepolizumab or benralizumab for at least 24 weeks were included in this analysis. 65/157 (41.4%) would have also been eligible for omalizumab at the time of biologic initiation. No baseline differences in blood eosinophils, total IgE, FeNO, FEV1, ACQ6, mAQLQ, or exacerbation rate were observed between eligible and ineligible groups. An atopic phenotype was more common with omalizumab-eligible patients and an adult-onset phenotype was more common in ineligible patients (both p<0.001). At 24 weeks significant improvements were observed in the overall cohort in exacerbation rates, ACQ6, mAQLQ and reductions in prednisolone exposure with anti-IL5/5R therapies (all P<0.05), however, no significant differences between omalizumab-eligible and -ineligible groups were seen in any clinical outcome measure evaluated (see table for full results). Conclusion: In a large cohort of 157 patients with SEA, 41% are eligible for both an anti-IgE and anti-IL-5/5R approach. In a real-world setting, the clinical effectiveness of mepolizumab and benralizumab does not appear to be influenced by eligibility for omalizumab therapy. It remains unclear which SEA patients may respond better to an anti-IgE vs anti-IL5/5R approach when both treatments are an option.